Sensitivity of the BEAM4 fisheries bioeconomic model to the main biological input parameters - de Castro, LAB; Petrere, M.; Comune, A. E. (Elsevier B.V., 2001)
Several runs of the BEAM4 model were carried out, combining several sets of input parameters from von Bertalanffy's growth curve (Lt = L-x[1 - e(-k(-to))]) and the natural mortality (M), with sets or parameters from the length-weight relationship (W=aL(b)). Further simulations were made with variations of +/- 20%, in the input parameters: recruitment (R), catchability coefficient (q), and the lengths at which 50 and 75% of the fishes are retained by the net (L-50%, and L-75%). The data used were those of the pair trawl fisheries for corvina Micropogonias furnieri, off southeastern Brazil. Results showed variations in the output (landed weight) ranging from - 62 to 147% associated with the diverse sets of VBGF and LWR parameters, and lower variations associated with the other input parameters tested. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: BEAM4; bio-economic model; fisheries model; sensitivity